Sistem Informasi Wisata dan Budaya Pulau Lombok dengan Multimedia Intraktif Untuk Meningkatkan Kunjungan Wisata - Hariman Bahtiar (Fakultas Teknik Universitas Hamzanwadi, 2018)
Information systems using multimedia technology are more effective because multimedia-based information systems can improve performance and increase information effectiveness. Careful and careful design is an absolute requirement for successful use of multimedia technology. In the world of information, the use of multimedia is more used because multimedia can eliminate saturation by utilizing a visualization display that can be enjoyed and able to give the impression of life with animation. This multimedia information system about tourism and culture of Lombok Island is expected to provide benefits to those in need.DOI : 10.29408/jit.v1i1.877